2012
DOI: 10.1016/j.jcrs.2011.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of cataract surgery in patients with neovascular age-related macular degeneration in the era of anti-vascular endothelial growth factor therapy

Abstract: With regular evaluations and appropriate treatment with anti-VEGF agents, cataract surgery did not appear to be associated with an increased incidence of perioperative complications or macular adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 17 publications
5
34
0
1
Order By: Relevance
“…Furino et al 10 showed favorable results one month after combined phacoemulsification and bevacizumab in an active exudative AMD setting. Tabandeh et al 11 reported similar visual acuity gains in a follow-up period that was shorter than twelve months, in patients that had phacoemulsification whilst being treated with either ranibizumab or bevacizumab. Like Tabandeh et al, we included patients that at the time of the cataract surgery procedure were being treated with either ranibizumab or bevacizumab.…”
Section: -11mentioning
confidence: 85%
See 1 more Smart Citation
“…Furino et al 10 showed favorable results one month after combined phacoemulsification and bevacizumab in an active exudative AMD setting. Tabandeh et al 11 reported similar visual acuity gains in a follow-up period that was shorter than twelve months, in patients that had phacoemulsification whilst being treated with either ranibizumab or bevacizumab. Like Tabandeh et al, we included patients that at the time of the cataract surgery procedure were being treated with either ranibizumab or bevacizumab.…”
Section: -11mentioning
confidence: 85%
“…In an era in which exudative AMD can be treated successfully with anti-vascular endothelial growth factor (VEGF) drugs few studies have addressed cataract surgery in patients being treated with these agents. [7][8][9][10][11] It is important to understand the effect of cataract surgery and concomitant anti-VEGF therapy on exudative AMD.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Each of these prior analyses was limited to a small cohort of 30 eyes or fewer undergoing cataract surgery with prior IVT. [18][19][20] In this series, we reviewed a cohort of 197 eyes with prior injections along with an equal number of matched control eyes without prior injections. Only eyes with prior injections performed at the Duke Eye Center were included to ensure complete retrospective analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that neovascular AMD, can compromise in 90% of cases severely the vision (20/200 or worse) if left untreated [37], but with the advent of anti-vascular Endothelial Growth Factor (anti-VEGF) intravitreal injections as therapy in wet AMD has got stabilize (90%) or even improved vision (30%) in a large number of cases [38][39][40][41][42][43].…”
Section: Neovascular Amdmentioning
confidence: 99%
“…More recently, studies published have not showed an increase in recurrence, number of injections or worsening of visual acuity when compared with non-operated eyes [15,16,[25][26][27][39][40][41][42][43][50][51][52][53][54][55][56]. However, Lee and cols.…”
Section: Neovascular Amdmentioning
confidence: 99%